ADULT EDUCATION FOR CONSCIOUSNESS RAISING, GOOD NEIGHBORLINESS AND SUSTAINABLE DEMOCRACY AND LIVELIHOOD IN NIGERIA - Usman, Ya'u Haruna (Sokoto Educational Review, 2015)
Friendly neighborliness is an instrument for peaceful co-existence and harmonious relationship. It is also very vital to the sustenance of democracy and livelihood in every society. Unfriendly neighborliness is mostly caused by conflicts, especially when they escalate to violence. The Nigerian nation has witnessed several conflicts stemming from religious, ethnic, political and economic reasons. The effects of such conflicts are enormous; apart the loss of lives and property, resulting into many people deserting their homes, jobs and other sources of livelihood. The major repercussion of those conflicts is the intendments of hatred, fear, suspicion and unfriendly neighborliness among people living in such communities. Adult Education has numerous programmes that raise consciousness as well as solve the problems of ignorance, poverty, frustration among adults and youths in Nigeria. Peace education which is also an integral part of adult education can be used to raise the consciousness of the Nigerian adults and youths against violence. This type of education inculcates the virtues of tolerance and forgiveness; it also highlights the dangers of conflicts and the need for peaceful co-existence needed for the sustenance of democracy and livelihood in Nigeria.